THEORETICAL BASIS OF CLUSTER CREATION: INTERNATIONAL AND NATIONAL EXPERIENCE - Волковська, Г. Г.; Яновський, П. О. (Science-based technologies, 2013)
International experience of clusters structure creation is analysed, also the pre-conditions for their implementation on the territory of Ukraine are defined. The main problems of clusters formation and functioning are characterized. The basis of world cluster creation is identified, in such courtiers as Italy, USA, Germany, Britain, France, Finland, Japan and CIS countries. The peculiarities of world cluster forms are recognized, and also examples of successful implementation of clusters strategy in world experience are categorized. The most famous world clusters are qualified. The basis of Ukrainian cluster creation is analysed. The historical basis of such form of cooperation is identified and first experience of cluster form implementation on the territory of Ukraine is characterized